2015
DOI: 10.1186/s13643-015-0120-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of education to facilitate knowledge about chronic pain for adults: a systematic review with meta-analysis

Abstract: BackgroundChronic pain can contribute to disability, depression, anxiety, sleep disturbances, poor quality of life and increased health care costs, with close to 20 % of the adult population in Europe reporting chronic pain. To empower the person to self-manage, it is advocated that education and training about the nature of pain and its effects and how to live with pain is provided. The objective of this review is to determine the level of evidence for education to facilitate knowledge about chronic pain, del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
71
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 34 publications
(137 reference statements)
0
71
0
3
Order By: Relevance
“…Of note, the question about belief was asked after all participants had been provided with a biopsychosocial explanation of their pain in the introductory session. Given that only 29% of people reported a multifactorial understanding of pain cause, this one-off education session appeared insufficient to change beliefs, as suggested by other studies (56). Research on belief formation about pain cause has noted that healthcare providers, especially general practitioners (GPs) are a trusted source for such information and are likely to strongly influence patient beliefs (57,58).…”
Section: Discussionmentioning
confidence: 95%
“…Of note, the question about belief was asked after all participants had been provided with a biopsychosocial explanation of their pain in the introductory session. Given that only 29% of people reported a multifactorial understanding of pain cause, this one-off education session appeared insufficient to change beliefs, as suggested by other studies (56). Research on belief formation about pain cause has noted that healthcare providers, especially general practitioners (GPs) are a trusted source for such information and are likely to strongly influence patient beliefs (57,58).…”
Section: Discussionmentioning
confidence: 95%
“…Some research has shown that intense PNE interventions are more effective [51]. However, the effectiveness of PNE as an isolated treatment technique is limited [47] and its effects increase when combined with a targeted PE program [52,53]. PE is a first-choice treatment in the management of CMP [9][10][11][12][13][14], and PE in particular has proven to be a useful tool in the treatment of CMP.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence suggests that PNE can be effective for pain and function -physical, psychological and social [3,4,5,6,7,8,9]. While most studies have focused on changes in these outcomes, less attention has been paid to exploring the mechanisms by which PNE works.…”
Section: Introductionmentioning
confidence: 99%